2020
DOI: 10.21608/sinjas.2020.86367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irrigation Levels and Soil Amendment on Growth and Yield of Sweet Pepper Crop Under El-Arish Region Conditions

Abstract: Two field experiments were carried out during summer seasons of 2017 and 2018 at the Experimental Farm, Faculty of Environmental Agricultural Sciences, Arish University, Egypt to study the effect of three levels of irrigation (100, 80 and 60% of irrigation water requirement) and three types of soil amendments (without, gypsum and pressed olive cake) and their combinations on growth and yield of sweet pepper (Capsicum annuum L. cv. "Top Star") crop under El-Arish region conditions. Plants were irrigated using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The positive effect of the interaction between full irrigation and different soil amendments is widely documented. For instance, Badawi et al (2020) reported from a two‐season study that the interaction between the 100% irrigation requirement and pressed olive cake gave a significantly higher pepper yield and fresh and dry shoot weights compared with the 60% irrigation requirement in the control treatment. Moreover, 100% of the irrigation requirement with pressed olive cake produced significantly taller plants and more leaves than 60% of the irrigation requirement in the control treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of the interaction between full irrigation and different soil amendments is widely documented. For instance, Badawi et al (2020) reported from a two‐season study that the interaction between the 100% irrigation requirement and pressed olive cake gave a significantly higher pepper yield and fresh and dry shoot weights compared with the 60% irrigation requirement in the control treatment. Moreover, 100% of the irrigation requirement with pressed olive cake produced significantly taller plants and more leaves than 60% of the irrigation requirement in the control treatment.…”
Section: Discussionmentioning
confidence: 99%